Kin Recognition in the Parasitic Plant Triphysaria versicolor Is Mediated Through Root Exudates - Wang, Yaxin; Murdock, Maylin; Lai, Seigmund Wai Tsuen; Steele, Daniel B.; Yoder, John I. (Frontiers in Plant Science, 2020)
Triphysaria is a facultative parasitic plant in the Orobanchaceae that parasitizes the roots of a wide range of host plants including Arabidopsis, Medicago, rice and maize. The important exception to this broad host range is that Triphysaria rarely parasitize other Triphysaria. We explored self and kin recognition in Triphysaria versicolor and showed that exudates collected from roots of host species, Arabidopsis thaliana and Medicago truncatula, induced haustorium development when applied to the roots of Triphysaria seedlings in vitro while those collected from Triphysaria did not. In mixed exudate experiments, Triphysaria exudates did not inhibit the haustorium-inducing activity of those from host roots. Interestingly, when roots of Triphysaria seedlings were treated with either horseradish peroxidase or fungal laccase, the extracts showed haustorium-inducing factor (HIF) activity, suggesting that Triphysaria roots contain the proper substrates for producing HIFs. Transgenic Triphysaria roots overexpressing a fungal laccase gene TvLCC1 showed an increased responsiveness to a known HIF, 2,6-dimethoxy benzoquinone (DMBQ), in developing haustoria. Our results indicate kin recognition in Triphysaria is associated with the lack of active HIFs in root exudates. Treatment of Triphysaria roots with enzymatic oxidases activates or releases molecules that are HIFs. This study shows that exogenously applied oxidases can activate HIFs in Triphysaria roots that had no previous HIF activity. Further studies are necessary to determine if differential oxidase activities in host and parasite roots account for the kin recognition in haustorium development.